The importance of studying the images of architecture in miniature to recreate the appearance of the medieval baths of Shakhrisabz - Aziza Raupova (Genius Journals, 2022)
In this article, miniatures by Kamoliddin Bekhzad and other artists of the Timurid and post-Timurid eras are considered as a source on the architecture of medieval baths. Depicting the external and internal structure and decoration of baths, they, along with historical sources and little-studied archival materials, can play an important role in restoring the former appearance of the interior and exterior of the medieval baths of Shakhrisabz.
Keywords: Miniatures of Kamoliddin Bekhzad; Timurid; epochs; medieval baths of Shakhrisabz